2012
DOI: 10.1177/1745691612460688
|View full text |Cite
|
Sign up to set email alerts
|

Replications in Psychology Research

Abstract: Recent controversies in psychology have spurred conversations about the nature and quality of psychological research. One topic receiving substantial attention is the role of replication in psychological science. Using the complete publication history of the 100 psychology journals with the highest 5-year impact factors, the current article provides an overview of replications in psychological research since 1900. This investigation revealed that roughly 1.6% of all psychology publications used the term replic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

18
290
4
13

Year Published

2016
2016
2018
2018

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 623 publications
(361 citation statements)
references
References 24 publications
18
290
4
13
Order By: Relevance
“…Consistent with findings from other fields (see Makel et al, 2012;Makel & Plucker, 2014), Makel et al (2016) and Lemons et al (2016) reported that only 0.5% and 0.4%, respectively, of articles published in special education were replication studies; and most of those were conceptual replications, which do not directly test the validity of previous findings. Although other reviews (Banerjee, Movahedazarhouligh, Millen, & Luckner, 2018;Cook, Collins, Cook, & Cook, 2016;PROMOTING OPEN SCIENCE 11 Therrien, Matthews, Hirsch, & Solis, 2016) indicated that special education researchers often conduct studies that conceptually replicate at least some aspects of previous studies, these authors found that special education researchers (a) seldom explicitly identify the purpose of their research as replication, and (b) almost never conduct direct replications.…”
Section: The Nature Of the Special Education Researchsupporting
confidence: 75%
See 1 more Smart Citation
“…Consistent with findings from other fields (see Makel et al, 2012;Makel & Plucker, 2014), Makel et al (2016) and Lemons et al (2016) reported that only 0.5% and 0.4%, respectively, of articles published in special education were replication studies; and most of those were conceptual replications, which do not directly test the validity of previous findings. Although other reviews (Banerjee, Movahedazarhouligh, Millen, & Luckner, 2018;Cook, Collins, Cook, & Cook, 2016;PROMOTING OPEN SCIENCE 11 Therrien, Matthews, Hirsch, & Solis, 2016) indicated that special education researchers often conduct studies that conceptually replicate at least some aspects of previous studies, these authors found that special education researchers (a) seldom explicitly identify the purpose of their research as replication, and (b) almost never conduct direct replications.…”
Section: The Nature Of the Special Education Researchsupporting
confidence: 75%
“…Unfortunately, replication studies are seldom conducted (Makel, Plucker, & Hegarty, 2012;Makel & Plucker, 2014). Interestingly, when researchers have conducted replication studies, results have often failed to validate original findings (Camerer et al, 2016, in press;Ebersole et al, 2016;Klein et al, 2014;Open Science Collaboration, 2015).…”
Section: Concerns About the Culture Of Contemporary Sciencementioning
confidence: 99%
“…In contrast to the above, until recently replication studies have been very rare in many scientific fields; lack of replication efforts has been a particular problem in the psychological sciences (Makel et al, 2012), but this may hopefully change now with the wide attention that replication has received (Aarts et al, 2015).…”
Section: The Origins Of Nhst As a Weak Heuristic And A Decision Rulementioning
confidence: 99%
“…In psychology most replications are conceptual and not direct. Makel et al (2012) systematically analyzed articles in the top 100 psychology journals since 1900, and they found that only 1.07% of them reported replication attempts. And even worse, only 14% of all replications were direct replications.…”
Section: Replicability Controversies Revisitedmentioning
confidence: 99%